Structural basis for the inhibition of coronaviral main proteases by PF-00835231 - Zhou Xuelan; Lu Xiaolu; Lin Cheng; Zou Xiaofang; Li Wenwen; Zeng Xiangyi; Wang Jie; Zeng Pei; Wang Weiwei; Zhang Jin; Jiang Haihai; Li Jian (Acta Biochimica et Biophysica Sinica)
The main protease (Mpro) of coronaviruses plays a key role in viral replication, thus serving as a hot target for drug design. PF-00835231 is a promising inhibitor of SARS-CoV-2 Mpro. Here, we report the inhibitory potency of PF-00835231 against SARS-CoV-2 Mpro and seven Mpro mutants (G15S, M49I, Y54C, K90R, P132H, S46F, and V186F) from SARS-CoV-2 variants. The results confirm that PF-00835231 has broad-spectrum inhibition against various coronaviral Mpros. In addition, the crystal structures of SARS-CoV-2 Mpro, SARS-CoV M pro, MERS-CoV Mpro, and seven SARS-CoV-2 Mpro mutants (G15S, M49I, Y54C, K90R, P132H, S46F, and V186F) in complex with PF-00835231 are solved. A detailed analysis of these structures reveals key determinants essential for inhibition and elucidates the binding modes of different coronaviral Mpros. Given the importance of the main protease for the treatment of coronaviral infection, structural insights into M pro inhibition by PF-00835231 can accelerate the design of novel antivirals with broad-spectrum efficacy against different human coronaviruses.